An information model for the traditional long-roof typed malay houses - Embi, Mohamed Rashid; Said, Suzana (Faculty of Built Environment, UTM, 2008)
An information model has been developed for the study of traditional Malay houses (TMH) of the bumbung panjang type that is capable of being implemented in a computing environment. The information model consists of interpretive and generative sub-systems. The interpretive sub-system utilizes the formal approach of shape grammar in the analysis of the forms and spaces of the TMH while the generative sub-system utilizes the construction knowledge of the TMH to create the shapes of the TMH. This information model is implemented in a scene-graph modeling package which allow the users to modify design parameters such as type of spaces and length of timbers to either recreate an existing TMH or create a new TMH. The prototype implementation of the information model is currently limited to the timber-frame structure of the TMH.